An Investigation into Teachers and Parents’ Perspectives of the Introduction of Active Homework in Primary Schools. - Ronayne, Tara (Marino Institute of Education, 2020)
The purpose of this study is to explore parents and teachers’ perceptions of the implementation of active homework in primary schools. Physical inactivity has been recognised as a leading risk factor for global mortality and it is estimated this results in more than two million deaths each year. In Ireland, one in four children are classified as being obese. Given these obesity rates and the matter of schools being identified as primary sites for promoting physical activity, only limited research has been conducted in relation to active homework. A qualitative approach was used during this investigation where data was gathered using questionnaires. Two separate groups of participants were used during this research which included eighty-four parents and fourteen teachers. The data was analysed using thematic analysis. The study found that 17% of children participated in no physical activity after school and only 12% of children met the recommended 60 minutes of physical activity per day. The findings suggest that 80% of parents and 86% of teachers are in favour of implementing active homework in their schools. The participants cited the development of skills, creation of healthy habits and improving physical and mental health as benefits to active homework. In addition, parents and teachers acknowledged challenges to the implementation of active homework which included the poor recognition of physical education (PE), difficulties in monitoring homework completion, busy schedules and lack of interest. Teachers also reported “lacking experience in the area”. Finally, 83% of parents stated they would participate in active homework with their children and 100% of teachers expressed their belief that parents should participate in active homework due to their influential role in children’s lives. The study concludes that active homework is strongly supported by both parents and teachers alike, with mutual recognition of its global health benefits. However, there is a need for continuous professional development for teachers to increase their understanding of active homework and their ability to implement it into their teaching. Finally, further research should be conducted on a larger scale to pinpoint how to best implement active homework and the benefits associated with its completion.
Keywords: Research Subject Categories